Acute necrotic disorder of the small intestine post‐coronavirus disease‐2019 vaccination. Issue 1 (5th June 2022) - Nishimura, Tomoyuki; Onogawa, Seiji; Yamamoto, Takuya; Okuda, Yasuhiro; Ikeda, Morito; Matsumoto, Nozomu; Kurihara, Keisuke; Shimizu, Akinori; Kitamura, Shosuke; Katamura, Yoshio; Hirano, Naomichi; Itamoto, Shingo; et al.
Abstract: The Pfizer‐BioNTech coronavirus disease 2019 (COVID‐19) vaccine is extensively used worldwide, and its safety has been proven. Herein, we report a case of an acute necrotic disorder in the small intestine post‐COVID‐19 vaccination. The patient developed severe abdominal pain the day after the first vaccination. Contrast‐enhanced computed tomography showed extensive ileum wall thickening and ascites. Colonoscopy revealed a ring‐shaped ulcer and stricture in the terminal ileum. Ileocecal resection was performed, and the patient did not have further episodes of a necrotic disorder in the small intestine. Although it is unknown if this event is associated with vaccination, and this occurrence also does not outweigh the efficacy and safety of the Pfizer‐BioNTech COVID‐19 vaccine, gastroenterologists need to be aware of this rare case, given its noteworthy timing.